Practiced, Conceived and Lived space in the Postdigital City - Alvaro, Sandra (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
The pandemic has highlighted the fast transmission of needs, goods and ideas that sustain the functionality of our globalised, networked world. At the same time, it has highlighted the resilience and unbreakability of this network when transporting undesirable events such as fake news or a virus. Henceforth, this situation has forced us to rethink how we plan our inhabited space. Since the inception of ubiquitous computing, the city has mutated under a new technologically mediated functionalism, overlaid by the platforms of a global and highly relational system that is submitting space to the logic of computing. Fruit of previous doctoral research, this article reviews the transformations leading to the constitution of this technologically mediated urban space and analyses them by applying Lefebvre’s Unitarian Theory of Space. The objective is to unveil the challenges of the postdigital urban space and present projects that point towards alternative possibilities for urban planning.